Strategies for Gully Stabilization and Highland Protection in Chinese Loess Plateau - Liu, Wanfeng; Zhang, Huyuan; Zhu, Jianghong; Hu, Aiping (Frontiers in Earth Science, 2022)
Loess tablelands are large-scale platform with flat top surface in the central Chinese Loess Plateau, such as Dongzhiyuan with maximum thickness of loess strata more than 200m and as large as 900km2. It is the fast retreat of gully system around that make the loess tablelands broken, resulting in serious social and economic problems. In order to protect the safety of the farmland, buildings, roads, and pipelines nearby the gully head areas, a project named gully-head stabilization and loess-platform protection, shortly GSLP project, was launched by local government. This paper intends to outlines the multidisciplinary measurements against georisks involved with Dongzhiyuan loess tableland. Initial protection was concentrated on three belts, the tableland surface, slopes, and gully channels. Followed by gully head stabilization to control the fast retreat of gully systems. In the last decade, urban flood drainage system was improved to collect rainwater from loess tableland into artificial lakes as waterscape, and deliver the overflowing water down to gullies through constructed channels. Gully head expansion was estimated by different methods such as back calculation from erosion modulus, literature archaeology, or field monitoring. Large gullies expanded toward upstream direction with a rate between 0.45-6.56m/yr in the last 2000 years, while the small gullies retreated as fast as 7.5-27.0 m/yr just after a single rainstorm event. Big difference in gully retreat perhaps derivates from complicated combination of erosion processes, upstream catchment and the rainfall characteristics. A giant loess embankment was backfilled across a gully for convenient urban transportation, which provides a successful reference of gully head stabilization to GSLP project in other area of Chinese Loess Plateau.